Manajemen sumber daya manusia di SD Sumbangsih dan SMK Citra Negara - Raka Aji Ramdani; Iswanto; Chandra Sagul Haratua (Lancar Media Komunikasi, 2023)
will discuss several main topics in human resource management, including recruitment and selection of employees so that teaching and learning activities are of high quality, training and development of employees in teaching and learning activities, performance management in school activities, and the school environment, which of course in teaching and learning activities so as not to If you are bored, of course you need a reflection from extra activities at school such as ice breaking, motivators at school, games at school or extra-curricular programs at school as sensory and motor cell development. In the employee recruitment and selection section for teaching and learning activities, ways to attract highquality employees and select the right employees for available positions will be discussed. Employee training and development will discuss strategies to develop employee skills and knowledge so that they can make a greater contribution to the organization. Performance management will discuss how managers can monitor employee performance to improve teaching and learning activities, provide a comfortable school environment as feedback and rewards, and identify areas for improvement. Finally, employee compensation and benefits will discuss strategies for providing fair compensation and attractive benefits to employees, including policies on salary, health insurance, leave, and benefits to provide extra activities at school